The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1600-0609.2010.01548.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of peripheral blood values and bone marrow findings on prognosis for patients with essential thrombocythemia and polycythemia vera

Abstract: The Philadelphia chromosome-negative (Ph-) chronic myeloproliferative neoplasms include the three well-known clinical entities polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). Over time, patients with ET and PV may develop myelofibrosis (MF), and all three entities carry a risk of transformation into acute myeloid leukemia (AML). In a population-based survey during 1983-1999, we studied a total of 358 patients who were diagnosed with ET and PV in the city of Gothenburg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 39 publications
5
48
0
6
Order By: Relevance
“…However, BMF grade was not associated with worse overall survival. 52 These results were replicated in another study by Campbell et al in which 311 patients with essential thrombocythemia were included. Again, increased reticulin BMF grade at diagnosis was not significantly associated with poorer overall survival.…”
Section: Essential Thrombocythemia/polycythemia Veramentioning
confidence: 74%
“…However, BMF grade was not associated with worse overall survival. 52 These results were replicated in another study by Campbell et al in which 311 patients with essential thrombocythemia were included. Again, increased reticulin BMF grade at diagnosis was not significantly associated with poorer overall survival.…”
Section: Essential Thrombocythemia/polycythemia Veramentioning
confidence: 74%
“…1,4,5 In a recently published study, an even more increased incidence was found in 143 PVSG-defined PV patients, including slight reticulin fibrosis in approximately 20% and moderate to marked fibrosis in 51% of cases. 6 In contrast to these relatively high frequencies at presentation, other larger series reported lower ranges between 10% and 20%, with a significant prevalence of a minor fiber grade. 2,[7][8][9] In this context, scant knowledge is available regarding the precise relationship of initial BM fibrosis and clinical activity of PV.…”
Section: Introductionmentioning
confidence: 88%
“…2,[7][8][9] In this context, scant knowledge is available regarding the precise relationship of initial BM fibrosis and clinical activity of PV. 1,6 To date, it has not been clear whether a minor increase in reticulin fibrosis indicates a later stage of disease or a more aggressive course with a more rapid evolution into the so-called spent phase (post-PV myelofibrosis). In the 25 patients of the PVSG study with marked to moderate fibrosis, follow-up examinations failed to reveal a predictive value, and sequential biopsies showed that myelofibrosis may be present for a long time before onset of spent-phase PV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В одном из них было показано, что снижение содержания ретикулина и низкая кле-точность костного мозга связаны с артериальными тромбозами (АТ), но не с венозными (ВТ) [17]. В про-тивоположность этому в ходе другого исследования было выявлено, что начальные признаки фиброза значимо коррелируют с низкой частотой массивных АТ и ВТ [18].…”
Section: Introductionunclassified